Improving administrative decisions through expert systems: Empirical analysis - Marwa Gaber Ahmed Fahim (Review of Economics and Political Science (REPS), 2018)
Purpose - The purpose of this paper is to introduce and identify the basic components, tasks and application areas of expert systems (ESs) as a decision support system that has been increasingly used in the business world lately and explore its potential for improving the effectiveness of administrative decisions in the public sector. Empirically, the paper explains the role of ESs in fostering decision-making processes at the Ministry of Investment and International Cooperation (MIIC) in Egypt. Design/methodology/approach - The design of this research is descriptive in the theoretical section and quantitative in the empirical one. Theoretically, the study adopted both the analytical approach and systems approach to demonstrate main concepts and relationships, while it conducted an empirical study to investigate the correlations in practice. Findings - The research concluded that the usage of ESs is deemed to be on the top of the technical solutions that might help public organizations develop their management quality and maintain competitive strength. In addition, the results proved that ESs contribute to administrative decisions at MIIC. Practical implications - The paper provides profitable findings and recommendations which can be applied by Egyptian public executives, in an attempt to ensure high quality and successful decisions using modern technology. Originality/value - This study has valuable implications for theory and practice together, as it offers numerous contributions to literature in the area of concern.
Keywords: 330; Expert systems; Decision support systems; Managerial decision making; Public sector reform; Ministry of investment and international cooperation in Egypt